Scheduling problems with a common due window assignment: A survey - Janiak, Adam; Kwiatkowski, Tomasz; Lichtenstein, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
In this article a survey of studies on scheduling problems with a common due window assignment and earliness/tardiness penalty functions is presented. A due window is a generalization of the classical due date and describes a time interval in which a job should be finished. If a job is completed before or after the due window, it incurs an earliness or a tardiness penalty, respectively.
Keywords: scheduling; due window assignment; earliness/tardiness; practical example